Insights into Safety and Connection in Relationships Provided by Psychoanalytic Treatment of Autistic Individuals. Issue 1 (2nd January 2022) - Harrison, Alexandra Murray
ABSTRACT: The creation of safety in a relationship is a prerequisite for the risk-taking required for developmental progress and therapeutic change. Psychoanalysts typically speak of safety in the analytic relationship in terms of verbal exploration of sources of the patient's anxiety, and the analyst's role in maintaining the frame. Yet it is clear that safety is not the same as the absence of threat, but is instead based on psychological safety as well as physical safety. Psychological safety – or safety with another person – requires the developmental capacity making social connections. The fields of infant research and neurodevelopment – particularly the work of Beatrice Beebe and Stephen Porges – have contributed significantly to this critical aspect of analytic work through their explications of stress regulation. Disorders of self-regulation – i.e. impairments in the capacity to manage stress and experience safety – are central to the neurodevelopmental disorder of autism. In addition, language and symbolization are typically compromised in individuals on the autism spectrum. Therefore, therapists working with individuals on the autistic spectrum must explore alternatives to language and symbols for creating a safe environment. These alternative methods of communication are what I call the "music and dance" of therapeutic action. In this article I will first discuss some relevant contributions from research in infancy and neurodevelopment. I will then use a clinical illustration of analytic work with a child on the autistic spectrum to demonstrate nonverbal and largely implicit bodily means of mutual regulation with a patient. This example not only applies to the treatment of autism, but also provides more general insights into methods of creating safety in the analytic dyad.